Savska obrečna krajina - Simoneti, Maja (Urbani izziv, 2001)
The article presents a summary of findings from a research project dealing with development possibilities of the riverbanks and spaces along the river Sava in Ljubljana. In order to avoid problems with individual development initiatives a structural development concept for decision-making was devised. The proposal defines urban and outer riverbanks with different character and programme offer. Daily urban leisure needs are satisfied nearby, intensive programmes with wider significance are on the left bank. The programmes are connected with a path. Protected areas are integrated in the concept as development structures. The research findings prove the sensibility of the comprehensive approach to the riverbanks for planning development.
Keywords: leisure; Ljubljana; prosti čas; protected areas; recreation; reke; rekreacija; river landscapes; Sava; zelene površine; zelenice